Generation Z's Response to Humanitarian Issues in Gaza, Palestine - Ernawati, Ernawati (Journal of Modern Islamic Studies and Civilization, 2025)
This study aims to determine the actions of Generation Z related to the global humanitarian tragedy in Gaza. The population of this study was all Generation Z students in Kendari City—data collection through the distribution of Google Forms. The number of questionnaires filled out was 200 responses. The research period was December 2023. The results showed that most Generation Z respond to humanitarian issues without interacting directly with others (such as boycotting, praying, giving alms, and uploading news/status). Gen Z prefers using social media more than discussing humanitarian issues directly. Around 91 percent of respondents know products affiliated with Israel, and 67 percent do boycotted action. One of the reasons respondents avoided the boycott was because they thought it would worsen the economy. Boycotting a product does not mean stopping consumption but shifting consumption from one brand to another or maintaining demand. Thus, the call for a boycott must be accompanied by a more concrete explanation of its economic impact besides religiosity and humanitarianism. Local businesses/MSMEs also need to be prepared to increase their popularity and market share in the face of shifting product demand due to the boycott.